2022
DOI: 10.1111/jnp.12285
|View full text |Cite
|
Sign up to set email alerts
|

Word finding, prosody and social cognition in multiple sclerosis

Abstract: Background: Impairments in speech and social cognition have been reported in people with multiple sclerosis (pwMS), although their relationships with neuropsychological outcomes and their clinical utility in MS are unclear. Objectives: To evaluate word finding, prosody and social cognition in pwMS relative to healthy controls (HC). Methods: We recruited people with relapsing MS (RMS, n = 21), progressive MS (PMS, n = 24) and HC (n = 25) from an outpatient MS clinic. Participants completed a battery of word-fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…There is evidence of processing speed and attention impairment during relapses ( Morrow et al, 2011 ) and mild executive dysfunction following acute use of corticosteroids ( Prado and Crowe, 2019 ), as in the present case. Moreover, performance in Attentional Matrices is also influenced by psychomotor speed, which was found to be associated with communication abilities ( Yap et al, 2022 ). More generally, several cognitive phenotypes regarding attention/executive functions, language, and multidomain deficits have been recently identified in MS patients and appear to be relevant for clinical purposes ( De Meo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of processing speed and attention impairment during relapses ( Morrow et al, 2011 ) and mild executive dysfunction following acute use of corticosteroids ( Prado and Crowe, 2019 ), as in the present case. Moreover, performance in Attentional Matrices is also influenced by psychomotor speed, which was found to be associated with communication abilities ( Yap et al, 2022 ). More generally, several cognitive phenotypes regarding attention/executive functions, language, and multidomain deficits have been recently identified in MS patients and appear to be relevant for clinical purposes ( De Meo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MS patients may show impairment also in language and communication abilities ( Sonkaya and Bayazit, 2018 ; Feenaughty, 2022 ). More in detail, a review by Renauld et al (2016) showed that MS is commonly associated with impaired performance in verbal fluency and sentence comprehension tasks, and later studies found that communication difficulties in MS are related to impairments in processing speed ( Yap et al, 2022 ) and in executive functioning ( Delgado-Álvarez et al, 2021 ). This evidence suggests an association between cognitive and linguistic domains.…”
Section: Introductionmentioning
confidence: 99%
“…In other recent studies, cognitive impairment may not be so severe, but definitely present with word finding difficulty and visual object naming [143]. The reduction in formation processing speed that is observed with cognitive loss in MS can be independent of mood disorders, and impairments in visual object meaning perception may appear uniquely in individuals with MS [143]. It is estimated that loss of cognitive function in MS occurs in approximately sixty-five percent of individuals and can affect processing of information, attention, memory recall, and other executive functions [144].…”
Section: Cognitive Loss and Dementia That Can Occur In Multiple Scler...mentioning
confidence: 72%
“…In some patient cohorts of MS that included both men and women, the prominent clinical phenotype was characterized by severe cognitive impairment that was progressive in nature [142]. In other recent studies, cognitive impairment may not be so severe, but definitely present with word finding difficulty and visual object naming [143]. The reduction in formation processing speed that is observed with cognitive loss in MS can be independent of mood disorders, and impairments in visual object meaning perception may appear uniquely in individuals with MS [143].…”
Section: Cognitive Loss and Dementia That Can Occur In Multiple Scler...mentioning
confidence: 99%
“…The majority of patients showed deficits at nonsocial tasks, particularly in the executive domains. www.nature.com/scientificreports/ and depression 31 . Three studies showed a significant positive correlation between aToM and cognition (higher aToM scores were associated with better performance on long-term storage and retrieval tasks, the Symboldigit-modalities test 32 ; and semantic fluency and IQ 27 ).…”
Section: (Continued)mentioning
confidence: 99%